Gelidium rosulatum (Gelidiales, Rhodophyta), a new species of subtidal marine algae from Korea. Issue 3 (4th May 2022) - Boo, Ga Hun; Park, Jeong Kwang; Han, Kyu Sam; Yoon, Hwan Su
ABSTRACT: Gelidium rosulatum, a new species from the subtidal zone in eastern Korea, is described on the basis of morphological observations and molecular analyses. Phylogenies of plastid rbc L and mitochondrial cox 1 markers revealed the distinctness of the new species, which was closely related to other East Asian species and G. chilense. Gelidium rosulatum is distinguished by a small thallus (up to 0.8 cm) that forms rosette turfs, leaf-like branchlets arising spirally along the erect axis, abundant rhizines in the medulla, cylindrical tetrasporangial sori without sterile margins, and rhomboid bilocular cystocarps borne on the apical parts of branchlets. The diversity of Korean Gelidium is now updated to 19 species, but further surveys of little explored areas and studies of dubious reports may reveal additional undescribed species.